Rhinovirus‐associated pulmonary exacerbations show a lack of FEV1 improvement in children with cystic fibrosis. Issue 2 (29th January 2016) - Cousin, Mathias; Molinari, Nicolas; Foulongne, Vincent; Caimmi, Davide; Vachier, Isabelle; Abely, Michel; Chiron, Raphael
Abstract : Background: Respiratory viral infections lead to bronchial inflammation in patients with cystic fibrosis, especially during pulmonary exacerbations. The aim of this study was to determine the impact of viral‐associated pulmonary exacerbations in children with cystic fibrosis and failure to improve forced expiratory volume in 1 s (FEV1 ) after an appropriate treatment. Methods: We lead a pilot study from January 2009 until March 2013. Children with a diagnosis of cystic fibrosis were longitudinally evaluated three times: at baseline (Visit 1), at the diagnosis of pulmonary exacerbation (Visit 2), and after exacerbation treatment (Visit 3). Nasal and bronchial samples were analyzed at each visit with multiplex viral respiratory PCR panel (qualitative detection of 16 viruses). Pulmonary function tests were recorded at each visit, in order to highlight a possible failure to improve them after treatment. Lack of improvement was defined by an increase in FEV1 less than 5% between Visit 2 and Visit 3. Results: Eighteen children were analyzed in the study. 10 patients failed to improve by more than 5% their FEV1 between Visit 2 and Visit 3. Rhinovirus infection at Visit 2 or Visit 3 was the only risk factor significantly associated with such a failure (OR, 12; 95% CI, 1·3–111·3), P = 0·03. Conclusions: Rhinovirus infection seems to play a role in the FEV1 recovery after pulmonary exacerbation treatment in children with cystic fibrosis. Such an association needs to be confirmed by a large‐scale study because this finding may have important implications for pulmonary exacerbation management.